Session 3: To What Extent Should Libraries Be Permitted to Engage in Mass Digitization of Published Works, and for What Purposes? - Aiken, Paul; Harbeson, Eric; Pilch, Janice T.; Phares, Gloria C. (The Columbia Journal of Law & the Arts, 2013)
Transcript of a symposium held at Columbia University about the legality of libraries digitizing published works and the purposes and potential consequences of libraries doing this. Focuses on section 108 of the copyright law as it pertains to mass digitization.